Economic Evaluation of Climate Change Impacts : Development of a Cross-Sectoral Framework and Results for Austria - Steininger, Karl W.; König, Martin; Bednar-Friedl, Birgit; Kranzl, Lukas; Loibl, Wolfgang; Prettenthaler, Franz (Springer Climate,, 2015)
This volume deals with the multifaceted and interdependent impacts of climate change on society from the perspective of a broad set of disciplines. The main objective of the book is to assess public and private cost of climate change as far as quantifyable, while taking into account the high degree of uncertainty. It offers new insights for the economic assessment of a broad range of climate change impact chains at a national scale. The framework presented in the book allows consistent evaluation including mutual interdependencies and macroeconomic feedback. This book develops a toolbox that can be used across the many areas of climate impact and applies it to one particular country: Austria. "This study is a landmark, setting a new standard for the assessment of the impacts of climate change. It stands out for the comprehensiveness of its coverage of potential impacts across different sectors of the economy and its methodological innovations, including tracing climate impacts to economic endpoints." Michael Hanemann, Professor of Economics, Arizona State University and Professor of the Graduate School, University of California, Berkeley "This volume develops a consistent, bottom-up approach for a robust evaluation across the whole range of impact fields, acknowledging their macroeconomic feedbacks and budgetary implications." Thomas Sterner, Professor of Economics, University of Gothenburg "The lasting value of this book will come from the methodology with its frameworks, consistent toolbox and comprehensive integration, as well as the lessons learnt and shared, exemplified through application in Austria." Roger Street, Director of UK Climate Impacts Programme, University of Oxford.